Meeting Report on “10th Anniversary Symposium on Inflammatory Skin Disease” - Shirin Emtenani; John F. Baines; Katja Bieber; Evelyn Gaffal; Stephanie Goletz; Gema Hernández; Misa Hirose; Markus Hoffmann; Pascal Joly; Henriette Kirchner; Jörg Köhl; Sripriya Murthy; et al. (JID Innovations)
The Lübeck Institute of Experimental Dermatology celebrated its 10th Anniversary Symposium on Inflammatory Skin Diseases at the University of Lübeck, Germany, on October 17–18, 2024. This event brought together international key opinion leaders, faculty members, researchers, and clinicians to foster insightful discussions on the diagnosis, pathomechanisms, and treatment of autoimmune skin diseases, with a particular focus on pemphigus, pemphigoid diseases, and systemic sclerosis.